Rehabilitasi Mangrove untuk Mendukung Perikanan Berkelanjutan dan Mitigasi Iklim di Desa Labuhan Kuris Kabupaten Sumbawa - Supriandi Supriandi; Neri Kautsari; Akbar Sapilin; Rahmawati Rahmawati; Ilham Syahputra; Agum Rhismanda; Tezar Rafandi; Teguh Dwi Dharmawan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The mangrove ecosystems in Labuhan Kuris Village, Lape Subdistrict, Sumbawa Regency are degraded. The area of mangrove ecosystems is categorized as good; it has decreased, potentially impacting the decline in fisheries' productivity, global warming, and other effects. This community service activity aims to rehabilitate mangroves through education and mangrove planting. The stages of this activity include an initial survey of community knowledge (pre-test) regarding mangroves, education and discussion sessions (talk shows), mangrove planting, and monitoring and evaluation. Meanwhile, the target audience for this activity is adult community members. Interviews using questionnaires were conducted to assess the community's initial understanding of mangroves. An educational session on the roles of mangroves was conducted by providing materials and distributing stickers about the roles of mangroves, and sessions. An evaluation of understanding levels was performed through post-tests, while monitoring and evaluation were conducted using direct observation methods in the field. Post-test results showed that 88% of the target audience understand the function of mangroves, 96% stated that mangroves ' role is to protect fish and crabs, while only 60% answered that mangroves have roles in climate mitigation. The number of participants in the educational session was 50 people. The mangrove species planted was Rhizophora sp. On this occasion, 1000 mangrove seedlings were planted, and the number of community members involved in mangrove planting was 220. Monitoring and evaluation results indicated that some plants were damaged due to trampling by livestock. Thus, mitigation was done by fencing around the planting area. Overall, the community actively participated from the beginning to the end of the activities. This condition indicates that the community is highly concerned about mangrove management. However, community participation in mangrove management should be improved.